Fuel Supply in Ljubljana During the Second World War - Šorn, Mojca (Inštitut za novejšo zgodovino, 2005)
After Italy occupied Ljubljana in April 1941, the fuel supply became limited, resulting in tin increased demand and price rise. This was not the only problem. During the war, due to worsening transport conditions and an ever growing need for coal by the railways, most of the coal transported to Ljubljana was intended for industry. Households were forced to use mainly firewood for their needs. Towards the end of the war firewood became a very scarce commodity in depots, hue! vouchers became practically useless. The citizens of Ljubljana had to fend for themselves as best they could. Po okupaciji je bil dovoz kuriva v Ljubljano omejen, kar je spodbudilo povpraševanje, hkrati pa tudi rast cen. To ¡pa ni bil edini problem. Zaradi čedalje bolj oteženih prometnih razmer in povečane potrebe železnice po premogu so v času vojne v Ljubljano v glavnem dovajali premog, namenjen le za industrijske obrate. Gospodinjstva so morala za svoje potrebe uporabljati predvsem drva. Teh je proti koncu vojne v skladiščih ostalo nezavidljivo malo. Nakaznice za kurivo so postale praktično nične. Ljubljančani so si po najboljših močeh pomagali sami.